The Biogeography of Fungal Communities Across Different Chinese Wine-Producing Regions Associated With Environmental Factors and Spontaneous Fermentation Performance - Li, Ruilong; Yang, Siyu; Lin, Mengyuan; Guo, Sijiang; Han, Xiaoyu; Ren, Mengmeng; Du, Le; Song, Yinghui; You, Yilin; Zhan, Jicheng; Huang, Weidong (Frontiers in Microbiology, 2022)
Chinese Marselan grapes are believed to possess the potential to become a characteristic regional variety, whose quality is internationally recognized. The fermentation-related mycobiota from six climatically diverse Marselan-producing regions in China were analyzed via high-throughput sequencing (HTS), while the influence of environmental factors was evaluated as well. The results implied that the phyla Ascomycota and genus Aureobasidium dominated the fungal communities in 166 Marselan must and fermented samples. Significant differences were detected in the fungal microbiota from the regions, as well as the wineries, while these discrepancies decreased as the fermentation progressed. Moreover, the discrepancy in fungal communities between the wineries exceeded the variation involving the regions. Geoclimatic elements (Gc) and physicochemical indexes (Pi) exerted a significant effect on the fungal must consortium, explaining 58.17% of the taxonomic information. Furthermore, a correlation was proposed between the spontaneous fermentation performance and their association with fungal taxonomic composition. In addition to depicting a fundamental landscape of fungal biogeography patterns across Chinese main wine-producing regions, we firstly proposed the correlation between the must polyphenol content and fungal microbiota, which may provide a new strategy for harnessing autochthonous “microbial terroir.”